A Comparative Analysis of the Protection of the Rights of Childhood Cancer Survivors to Education Under Special Education Law - Margaret Flood; Lisa Carey (Continuity in Education)
Access to equitable education for children treated for cancer is of growing international concern across education, medicine, and related fields. Neurocognitive late effects of childhood cancer and treatment are well established. This impact on cognition results in difficulties with thinking, learning, peer-relationships, and quality of life. Formalized In-School Supports (ISS) can ameliorate the negative impacts of neurocognitive late effects, yet the literature suggests that children treated for cancer often have difficulty accessing these services. This paper reviews the ISS legislation of eight countries regarding protections offered to children treated for cancer and evidence of access to ISS within the literature. The purpose of this review was to look for common barriers for children treated with cancer accessing educational support through ISS. This review identifies gaps between ISS student-focused disability legislation, and practice to inform positive policy change.